(untitled) (The Journal of Psychology and Sociology, 2025)
Improving methods of psychological testing is an urgent task due to the increasing use of remote testing and the need to refine the balance between phylogenetic and ontogenetic components of the psyche. These circumstances require the modernization of existing approaches to the design of psychological tests. The aim of this study is to develop a testing methodology focused on identifying hereditary components in an individual’s psyche. The central idea of the research is that consideration of hereditary and sociocultural factors can enhance the effectiveness of psychological diagnostics and psychotherapeutic practices. The scientific and practical significance of the study lies in the fact that the proposed methodology provides new opportunities for analyzing the mechanisms of manifestation of the sociocultural code and for improving psychotherapeutic tools. The research methodology is based on the use of neural network technologies to generate images on a given topic and to compare them within “mother–daughter” pairs. This approach makes it possible to identify correlations that reflect hereditary components of the psyche. The results demonstrate that the proposed methodology can effectively reveal hereditary elements of the psyche and support the neural network theory of social formation, according to which human consciousness has a dual nature that includes both individual and collective components. The contribution of this study consists in advancing the theoretical foundations of psychodiagnostics and in demonstrating the potential of artificial intelligence for identifying hereditary aspects of the psyche. The practical significance of the results lies in creating the basis for the development of new psychotherapeutic practices that take into account the influence of the sociocultural code on personality formation. Keywords: images, neural network, inherited ideas, mentality, spirit of the nation, transpersonal level of information processing, mentality.